PENERAPAN TERAPI BEKAM BASAH PADA PASIEN DENGAN KELUAHAN NYERI PUNGGUNG BAWAH DI RUMAH SEHAT ZEIN HOLISTIC THERAPY KOTA MAKASSAR - Irna Agustiani; Fatma Jama; Samsualam; Eliati Paturungi (CV. Adiba Aisha Amira, 2025)
Low back pain is a common health problem found in society, especially in primary healthcare facilities, and is even recognized as a leading cause of disability worldwide. The main cause of low back pain in young adults to adults is mostly caused by lumbar herniation. The purpose of the study was to find out an overview of the application of cupping therapy with complaints of low back pain in Mrs. J at the Zein holistic therapy health home in Makassar City The research method is a case study that describes a finding in one patient, Mrs. J with low back pain with acute pain nursing problems on August 12, 2025 at the Zein Holistic Therapy Clinic in Makassar City. Based on the results of the assessment on Mrs. J, acute pain is related to physical injury agents. The result of this activity is to implement a nursing care plan using SIKI, namely pain management with the administration of wet cupping therapy which is carried out for 1x24 hours with the results of evaluation obtained decreased pain complaints. Based on the results of the implementation and evaluation of the application of cupping therapy to reduce low back pain in Mrs. J, it was found that the lower back pain scale decreased from a pain scale of 4 (moderate) to a scale of 2 (mild). So that cupping therapy can be used as a nursing intervention in reducing pain in patients with lower back pain complaints.